Low Voltage Graphene-Based Amplitude Modulator for High Efficiency Terahertz Modulation - Qianying Zheng; Liangping Xia; Linlong Tang; Chunlei Du; Hongliang Cui (Nanomaterials, 2020)
In this paper, a high-efficiency terahertz amplitude modulation device based on a field-effect transistor has been proposed. The polarization insensitive modulator is designed to achieve a maximum experimental modulation depth of about 53% within 5 V of gate voltages using monolayer graphene. Moreover, the manufacturing processes are inexpensive. Two methods are adopted to improve modulation performance. For one thing, the metal metamaterial designed can effectively enhance the electromagnetic field near single-layer graphene and therefore greatly promote the graphene’s modulation ability in terahertz. For another, polyethylene oxide-based electrolytes (PEO:LiClO4) acts as a high-capacity donor, which makes it possible to dope single-layer graphene at a relatively low voltage.